Distance and Virtual Education: Teaching Challenges (Docentes 2.0 Journal, 2026)
Distance and virtual education in rural contexts gained prominence during the post-pandemic period, highlighting disparities in access to and use of learning technologies. This study aimed to analyze the pedagogical challenges, implemented strategies, and factors influencing student retention and learning at an upper-secondary agricultural institution. The research was framed within the positivist paradigm, employing a hypothetico-deductive method with a quantitative approach, a non-experimental design, a descriptive scope, and a cross-sectional nature. The study population consisted of 27 teachers and 96 students, from which a sample of 78 individuals was selected using simple random sampling. Surveys were utilized as the data collection technique, employing structured questionnaires featuring a 0-to-4 Likert-type scale, which were administered in a digital format. Data analysis was conducted using descriptive statistics, specifically frequencies and percentages. The results revealed that personal motivation and family support were the primary factors associated with student retention, whereas internet access constituted a significant limitation. Furthermore, pedagogical strategies focused on individual work, research, and the creation of academic products. It was concluded that distance education in rural contexts necessitates strengthening teacher training in digital tools and implementing contextualized strategies that foster effective learning.
Keywords: Virtual education; distance education; educational strategies; teacher challenges